1998
DOI: 10.1016/s0002-9270(98)00215-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and upper gastrointestinal motility features in systemic sclerosis and related disorders

Abstract: In patients with GI symptoms associated with systemic sclerosis and related disorders, the amplitude and frequency of intestinal contractions are typically <10 mm Hg and <2/min. Antral amplitude is low (<40 mm Hg) when antral hypomotility is observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
0
13

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 0 publications
3
62
0
13
Order By: Relevance
“…Since the initial description of an association between BE and SSc by Cameron and Payne in 1978 (15), numerous case reports (16-28) and 3 retrospective series (29)(30)(31) (Table 3) have been published. In the earliest retrospective series, the prevalence of BE was estimated to be 37% among patients who were assessed by endoscopy following reports of clinical gastrointestinal symptoms (30), and 16% among patients referred to a gastroenterology department (31). SSc patients who undergo endoscopy because of digestive symptoms may represent the subgroup with the most severe esophageal involvement, thus increasing the prevalence of BE.…”
Section: Discussionmentioning
confidence: 99%
“…Since the initial description of an association between BE and SSc by Cameron and Payne in 1978 (15), numerous case reports (16-28) and 3 retrospective series (29)(30)(31) (Table 3) have been published. In the earliest retrospective series, the prevalence of BE was estimated to be 37% among patients who were assessed by endoscopy following reports of clinical gastrointestinal symptoms (30), and 16% among patients referred to a gastroenterology department (31). SSc patients who undergo endoscopy because of digestive symptoms may represent the subgroup with the most severe esophageal involvement, thus increasing the prevalence of BE.…”
Section: Discussionmentioning
confidence: 99%
“…On histological examination, smooth muscle atrophy and fibrosis causing motor activity abnormalities in two-thirds of the distal esophagus are often determined (4). Motility studies have shown that the amplitude of peristaltic contractions decreases or that there is no peristaltic contraction in this region (5)(6)(7). Abnormal peristalsis and decreased lower esophageal sphincter (LES) pressure reduce acid clearance and prolong the contact of acid with the mucosa (8).…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…As a result, GERD develops in patients with scleroderma. In many cross-sectional studies using different methodologies, the prevalence of GERD has been reported to be at rates of up to 70% (9)(10)(11)(12)(13)(14)(15). (18), GERD prevalence was found to be 40.7%.…”
Section: Systemic Sclerosismentioning
confidence: 99%
“…Oko 90% bolesnika ima poremećaj gastrointestinalnog trakta (18)(19)(20). Plućna hipertenzija, pleuritis i intersticijalna fibroza su manifestacije zahvaćenosti pluća (21).…”
Section: Ključne Rečiunclassified